Serum IRAP, a Novel Direct Biomarker of Prediabetes and Type 2 Diabetes? - Trocmé, Candice; Gonnet, Nicolas; Di Tommaso, Margaux; Samouda, Hanen; Cracowski, Jean-Luc; Cracowski, Claire; Lambert-Porcheron, Stéphanie; Laville, Martine; Nobécourt, Estelle; Gaddhab, Chiraz; Le Lay, Allan; Bohn, Torsten; et al. (Frontiers in Molecular Biosciences, 2021)
Insulin resistance (IR), currently called prediabetes (PD), affects more than half of the adult population worldwide. Type 2 diabetes (T2D), which often follows in the absence of treatment, affects more than 475 million people and represents 10–20% of the health budget in industrialized countries. A preventive public health policy is urgently needed in order to stop this constantly progressing epidemic. Indeed, early management of prediabetes does not only strongly reduce its evolution toward T2D but also strongly reduces the appearance of cardiovascular comorbidity as well as that of associated cancers. There is however currently no simple and reliable test available for the diagnosis or screening of prediabetes and it is generally estimated that 20–60% of diabetics are not diagnosed. We therefore developed an ELISA for the quantitative determination of serum Insulin-Regulated AminoPeptidase (IRAP). IRAP is associated with and translocated in a stoechiometric fashion to the plasma membrane together with GLUT4 in response to insulin in skeletal muscle and adipose tissue which are the two major glucose storage sites. Its extracellular domain (IRAPs) is subsequently cleaved and secreted in the blood stream. In T2D, IRAP translocation in response to insulin is strongly decreased. Our patented sandwich ELISA is highly sensitive (≥10.000-fold “normal” fasting concentrations) and specific, robust and very cost-effective. Dispersion of fasting plasma concentration values in a healthy population is very low (101.4 ± 15.9 μg/ml) as compared to those of insulin (21–181 pmol/l) and C-peptide (0.4–1.7 nmol/l). Results of pilot studies indicate a clear correlation between IRAPs levels and insulin sensitivity. We therefore think that plasma IRAPs may be a direct marker of insulin sensitivity and that the quantitative determination of its plasma levels should allow large-scale screening of populations at risk for PD and T2D, thereby allow the enforcement of a preventive health policy aiming at efficiently reducing this epidemic.